2019
DOI: 10.1007/s00213-019-05281-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alcohol use disorder on cellular aging

Abstract: Rationale Human telomeres consist of tandem repeats at chromosome ends which protect chromosomal DNA from degradation. Telomere shortening occurs as part of natural aging; however, life stressors, smoking, drug use, BMI, and psychiatric disorders could disrupt cell aging and affect telomere length (TL). In this context, studies have evaluated the effects of alcohol consumption on TL; however, results have been inconsistent, which may reflect diverse drinking cut-offs and categorizations. Objectives To help cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 57 publications
(71 reference statements)
1
17
0
Order By: Relevance
“…Moderate beer consumption may even provide some benefit against cardiovascular disease [30]. While a meta-analysis reported that the results concerning alcohol consumption and LTL are unclear [31], a disorder with heavy alcohol use was associated with telomere shortening [32]. In the present study, moderate alcohol consumption category was associated with shorter telomeres, while low alcohol intake category was associated with lower proportion of short telomeres.…”
Section: Discussionmentioning
confidence: 42%
“…Moderate beer consumption may even provide some benefit against cardiovascular disease [30]. While a meta-analysis reported that the results concerning alcohol consumption and LTL are unclear [31], a disorder with heavy alcohol use was associated with telomere shortening [32]. In the present study, moderate alcohol consumption category was associated with shorter telomeres, while low alcohol intake category was associated with lower proportion of short telomeres.…”
Section: Discussionmentioning
confidence: 42%
“…To do that, the authors compared 260 patients with alcohol use disorder and 449 healthy controls. Yet, drinking behaviors were not associated with relative TL in both groups [ 42 ]. Finally, the present systematic review identified the study by Tannous and colleagues that compared relative TL in blood samples from 24 patients with alcohol use disorder and 25 controls.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, newborns from drinking women exhibited shorter relative TL than those born from non-drinking women (Figure 2B). [40] No association between alcohol consumption and relative TL Smoking status was associated with relative TL Liu et al, 2013 [41] No association between alcohol intake and relative TL No relationships of folate, choline, methionine, riboflavin, vitamin B6, vitamin B12, and polymorphisms involved in one-carbon metabolism with relative TL Martins de Carvalho et al, 2019 [42] Alcohol use disorder was associated with lower relative TL. However, drinking behaviors were not associated with relative TL A significant interaction between age and alcohol use disorder on relative telomere length was evident Needham et al, 2013 [43] No association between alcohol use and relative TL…”
Section: Pilot Studymentioning
confidence: 99%
“…As shown in Table 1, all studies applied a case–control design. The most represented countries were the United States with three studies [51–53] and Japan with two studies [54,55]. Case samples presented mean ages ranging between 26.2 and 74.5 years (mean = 47.4), whereas control samples ranged from 33.3 to 75.1 (mean = 55.1).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies included men only [55–57] and one study with two analysis units included women only [58]. Related to the type of substance used, five studies investigated alcohol [52–55,57], one alcohol and cocaine [51], one cocaine [58], one tobacco and marijuana [56], one a mixture of cocaine, heroin, methamphetamine and morphine [59] and one study did not describe the substances consumed by those diagnosed with SUD [60].…”
Section: Resultsmentioning
confidence: 99%